2021
DOI: 10.1007/s00268-021-06068-6
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality in Patients with Perioperative COVID‐19 Infection: Prospective Cohort in General, Gastroesophagic, Hepatobiliary, and Colorectal Surgery

Abstract: Background Severe acute respiratory syndrome due to coronavirus 2 has rapidly spread worldwide in an unprecedented pandemic. Patients with an ongoing COVID-19 infection requiring surgery have higher risk of mortality and complications. This study describes the mortality and morbidity in patients with perioperative COVID-19 infection undergoing elective and emergency surgeries. Methods Prospective cohort of consecutive patients who required a general, gastroesophageal, hepatobiliary, colorectal, or emergency su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 26 publications
(53 reference statements)
3
25
0
Order By: Relevance
“…Perioperative COVID-19 infection has negatively impacted the safety of patients undergoing surgery, increasing complications and mortality rates [ 1 , 4 ]. Currently, only a few studies have reported data on the risk of perioperative COVID-19 infection and safety outcomes in patients undergoing bariatric surgery during the ongoing pandemic [ 13 15 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Perioperative COVID-19 infection has negatively impacted the safety of patients undergoing surgery, increasing complications and mortality rates [ 1 , 4 ]. Currently, only a few studies have reported data on the risk of perioperative COVID-19 infection and safety outcomes in patients undergoing bariatric surgery during the ongoing pandemic [ 13 15 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is important to consider that the opening phase for bariatric surgery occurred when SARS-CoV-2 viral circulation levels were low; thus, we cannot extrapolate these results when circulating viral levels are higher. A strength of our study is that we have a 100% follow-up of all our 189 patients during the first 30 days after discharge, and we were able to use the same rigorous COVID-19 protocol and recommendations that we used in the early phases of the pandemic for unpostponable surgeries, with positive results [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30-day mortality and surgical complications are more common in patients with concomitant COVID-19 infection -in a total of 701 patients undergoing surgical treatment, 39 /5.6%/ of whom with perioperative CO-VID-19 infection, 30-day mortality was 12.8% and 1.4% in patients without COVID-19 infection, respectively (p < 0.001). It is appropriate in COVID-19 patients to perform only emergency surgical interventions in view of the increased risk of irreversible complications (Inzunza et al 2020). Patients who underwent surgery had a higher mortality rate if they were diagnosed with COVID-19 after surgery, than if they were diagnosed with COVID-19 before.…”
Section: Introductionmentioning
confidence: 99%